2013
DOI: 10.1186/cc13047
|View full text |Cite
|
Sign up to set email alerts
|

The adverse effect of emergency department crowding on compliance with the resuscitation bundle in the management of severe sepsis and septic shock

Abstract: IntroductionThe aim of this study is to evaluate the effects of emergency department (ED) crowding on the implementation of tasks in the early resuscitation bundle during acute care of patients with severe sepsis and septic shock, as recommended by the Surviving Sepsis Campaign guidelines.MethodsWe analyzed the sepsis registry from August 2008 to March 2012 for patients presenting to an ED of a tertiary urban hospital and meeting the criteria for severe sepsis or septic shock. The ED occupancy rate, which was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
38
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 33 publications
1
38
1
Order By: Relevance
“…10 In another study, the mean age was 65 and 56.8% were men. 11 In Pines et al study, 57.0% were men with the mean ± SD age of 44 ± 17 years. 12 In Nasr-Esfahani et al study, 484 patients were admitted to the ED with the mean ± SD age of 53.8 ± 20.3 which 55.8% were men.…”
mentioning
confidence: 89%
“…10 In another study, the mean age was 65 and 56.8% were men. 11 In Pines et al study, 57.0% were men with the mean ± SD age of 44 ± 17 years. 12 In Nasr-Esfahani et al study, 484 patients were admitted to the ED with the mean ± SD age of 53.8 ± 20.3 which 55.8% were men.…”
mentioning
confidence: 89%
“…Due to the importance of adherence to EGDT bundle, studies investigated factors associated with compliance (94,95). These studies showed that body temperature, experience of nurses and physicians, cryptic shock, serum lactate levels and ED crowding all affected adherence (94,96). An important distinction between RCTs exploring EGDT and observational studies applying the SSC bundle is that the latter included somewhat different components than recommended in EGDT.…”
Section: Compliance With Surviving Sepsis Campaign (Ssc) Bundlementioning
confidence: 99%
“…Other factors that decrease compliance with resuscitation guidelines include low awareness among healthcare workers, healthcare workforce shortages, overcrowding of emergency departments [13], and unfavourable nurse-to-patient ratios [14]. Low availability of resources can also limit the application of some interventions.…”
Section: Introductionmentioning
confidence: 99%